+0  
 
0
186
2
avatar

what does this equal?

 

(2*sqrt(2)*e^t)^2 =

Guest Sep 20, 2017

Best Answer 

 #2
avatar+86859 
+1

(2*sqrt(2)*e^t)^2

 

Notice that   2sqrt(2)   = sqrt (4 * 2)   =  sqrt (8)

 

So we have

 

[ sqrt (8) * e^t ] ^2   =

 

[sqrt (8) ]2 * [ e]2  =

 

8 * e2t

 

 

cool cool cool

CPhill  Sep 20, 2017
 #1
avatar+116 
0

\(({2}^{2}*{e}^{t})^2=16{e}^{2t}\)

MagikalRedNiteTiger  Sep 20, 2017
 #2
avatar+86859 
+1
Best Answer

(2*sqrt(2)*e^t)^2

 

Notice that   2sqrt(2)   = sqrt (4 * 2)   =  sqrt (8)

 

So we have

 

[ sqrt (8) * e^t ] ^2   =

 

[sqrt (8) ]2 * [ e]2  =

 

8 * e2t

 

 

cool cool cool

CPhill  Sep 20, 2017

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.